Kissing Fidel : A Memoir of Cuban American Terrorism in the United States - Montiel Davis, Magda, 1953- (Book collections on Project MUSE., 2020)
"What does it mean to be instantly transformed into the most hated person in your own community? After meeting Fidel Castro at a Havana reception, Cuban-born Magda Montiel Davis, founder of one of the largest immigration law firms in South Florida, soon found out. The reception-attended by hundreds of other Cuban emigres-was videotaped "for historical archives only." In a seconds-long clip, Fidel pecks the traditional protocol kiss on Magda's cheek and, based on Magda's many years of travel to the homeland, she thanks Fidel for the social benefits conferred upon the Cuban people. The video was sold to U.S. reporters and aired incessantly throughout South Florida, and the Magda-Fidel encounter tentacled as far as the international media, which promptly put an end to a free life for Magda and her family, including a father who worked with the CIA to topple Fidel, a no-hablo-ingles mother who lived with Magda, her five children, and Brooklyn-born husband, now known as Magdo. Forced to live under siege with the supposed protection of private bodyguards, Miami police, and FBI, Kissing Fidel shares the sometimes dismal, sometimes comical realities of an ordinary citizen being thrown into a world of death threats, mob attacks, and even drawings of Magda and Fidel in every imaginable Kama Sutra position"--